1960
DOI: 10.1079/bjn19600045
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and food consumption of pregnant women in a development area of Israel

Abstract: The purpose of the survey was to gain information on food habits and conditions and status of nutrition of pregnant women in one of Israel's development areas. These areas, the most important of which is the southern part of the country, called the Negev, with its capital Be'er-Sheba, are underpopulated and both economically and agriculturally underdeveloped ; there new immigrants are employed in road building, afforestation and other public works projects. On arrival they live in camps in small tin and wooden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1962
1962
1981
1981

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This diet contained 269 mg lysine, 75 mg methionine and 57 mg tryptophanlg nitrogen. Whereas lysine was found to be the critical amino acid in the proteins of mixed diets (Guggenheim, 1961)) it appears that in the vegetarian diets studied by us other amino acids, possibly methionine or tryptophan, limit the nutritional value of the proteins.…”
Section: K Guggenheim Y Weiss and M Fostickmentioning
confidence: 94%
See 2 more Smart Citations
“…This diet contained 269 mg lysine, 75 mg methionine and 57 mg tryptophanlg nitrogen. Whereas lysine was found to be the critical amino acid in the proteins of mixed diets (Guggenheim, 1961)) it appears that in the vegetarian diets studied by us other amino acids, possibly methionine or tryptophan, limit the nutritional value of the proteins.…”
Section: K Guggenheim Y Weiss and M Fostickmentioning
confidence: 94%
“…The protein efficiency ratio was only 1-27, considerably lower than those of two diets (1.76 and 1.93) consumed by middle-class Israelis (Guggenheim, unpublished). It is, however, interesting that the limiting amino acid in the vegetarian diet appeared not to be lysine, which limits the nutritive value of the proteins in both low-income and middle-class Israeli diets (Guggenheim, 1961). Whereas the latter contain 23 I-279 and 248-319 mg lysine/g nitrogen respectively, 375 mg lysine/g nitrogen were found in the average vegetarian diet.…”
Section: K Guggenheim Y Weiss and M Fostickmentioning
confidence: 98%
See 1 more Smart Citation
“…The interview covered the food eaten on the two previous days. Five week‐days and a Sabbath were included, in view of a previous finding that the Sabbath menu differed from the week‐day diet (1). A fluid measuring cup, measuring spoons and a spring balance were used as aids.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary studies in Israel have demonstrated the same difficulty. In one, in which women were interviewed about their diet on three separate days, Guggenheim, et al, 4 found that although they obtained records from most of their 164 subjects, only 100 appeared to be reliable. In another, in which concurrent dietary records were kept for a fortnight, Bavly5 found that even though the subjects were selected on the basis of their "cooperation, understanding and truthfulness," 10 per cent of the records had to be rejected.…”
mentioning
confidence: 99%